Global Citizenship in Social Studies Education - Kan, Cigdem (Pamukkale Univ, 2009)
The traditional citizenship definition is not adequate for such a period in which global developments are observed. Instead, universal or global citizenship concept has appeared. Global citizen has not yet been recognized in terms of legal identity meaning. However, as a morality and responsibility understanding, global citizen is the responsible citizen of not only his own country but also global world. One of the most basic goals of social studies lesson is to train citizens. Citizen to be raised should be global. Because, global developments necessitate to raise more active, responsible and democratic individuals when compared with past. The aim of this study is to seek an answer to the question of Why global citizenship education should be included into the social studies lesson?. Related literature has been reviewed in this research.
Keywords: Global Citizenship; Social Studies Lesson; Global Values